TINGKAT KEPUASAN MAHASISWA TERHADAP KINERJA DOSEN SEKOLAH TINGGI KEGURUAN DAN ILMU PENDIDIKAN (STKIP) MELAWI - Ason, Ason (STKIP Melawi, 2017)
Abstract: this research aims to know the level of satisfaction of studentsagainst the performance of a high school Professor of pedagogy andeducational sciences (STKIP) Melawi, by looking at the comparisonbetween prodi PGSD with PProdi Penjeskesrek analysis tool used wasmultiple linear regression, by taking the data using the method of giving adetailed questionnaire on respondent Melawi STKIP students. From theresults of the analysis of each of these variables can be noted that the levelof satisfaction of students STKIP Melawi prodi PGSD 54.65% andamounted to Penjaskesrek of prodi 52.4%. From the results of researchcan also note that the variable performance of lecturers include FactorsDiscipline wakti, Lecture Material Factors, factors of Strategy Evaluationfactor of lectures and Lecture was able to explain the level of satisfactionof students on performance lecturer STKIP Melawi of 53.53%. Thismeans of 46.47%. Student STKIP Melawi dissatisfied against academicservice STKIP Melawi. Thus the value of a performance lecturersimultaneously (simultaneous) affect the satisfaction of studentperformance against the professors, because the value of their significance< 0.05.Keywords: Student Satisfaction Rate, the performance of a lecturer.Abstrak : Penelitian ini bertujuan untuk mengetahui tingkat kepuasanmahasiswa terhadap kinerja dosen Sekolah Tinggi Keguruan dan IlmuPendidikan (STKIP) Melawi, dengan melihat perbandingan antara prodi PGSDdengan PProdi Penjeskesrek Alat analisis yang digunakan adalah regresi linierberganda, dengan mengambil data menggunakan metode memberikankuisioner pada responden mahasiswa STKIP Melawi. Dari hasil analisismasing-masing variabel dapat diketahui bahwa tingkat kepuasan mahasiswaSTKIP Melawi prodi PGSD sebesar 54,65% dan prodi Penjaskesrek sebesar 52,4%. Dari hasil penelitian juga dapat diketahui bahwa variable kinerja dosenyang meliputi Faktor Disiplin wakti, Faktor Materi Perkuliahan, Faktor StrategiPerkuliahan dan Faktor Evaluasi Perkuliahan mampu menjelaskan tingkatkepuasan mahasiswa terhadap kinerja dosen STKIP Melawi sebesar 53.53%.Ini berarti sebesar 46,47%. Mahasiswa STKIP Melawi tidak puas terhadaplayanan akademik STKIP Melawi. Dengan demikian maka nilai kinerja dosensecara bersama-sama (simultan) mempengaruhi kepuasan mahasiswaterhadap kinerja dosen, karena nilai signifikansinya < 0,05.Kata kunci: Tingkat Kepuasan Mahasiswa, Kinerja Dosen.